Nursing care at new mental health services - experience report - Tahissa Frota Cavalcante; Nirla Gomes Guedes; Rafaella Pessoa Moreira; Tatiane Gomes Guedes; Michell Ângelo Marques Araújo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The nursing attendance in mental health has been changing your paradigm, such as psychiatric remodeling and the new role assumed by the nurses. This study aims to describe the activities developed for a group of nursing academics during the practical process of teaching-learning applied at patients with mental disease in therapeutic phase. It is an experience report developed at a Psychosocial Support Center located at the city of Fortaleza-Ceará in the period held from September to November of 2004. The activities implemented by the academics were the group of community therapy, the wait room group and the therapeutic relationship. The community therapy and the therapeutic relationship obtained larger success due to the deep interaction between patients and academics, in addiction to the confort and sence of valuable the activities caused them. The development of the experience revealed itself important once it provided the mutual learning, obtaining satisfactory results and certainty that these activities are susceptible of implementation in other services.